Penerapan Model Pembelajaran Kooperatif Tipe STAD dalam Meningkatkan Minat dan Hasil Belajar Akuntansi (Studi pada Siswa Kelas XI Akuntansi SMK Negeri 2 Palu) - Suryani, Suryani (Jurnal Akun Nabelo : Jurnal Akuntansi Netral, Akuntabel, Objektif, 2018)
The problem of this research is the low of student interest and result of a study of accounting at the students of the class of XI Ak 1, SMKN 2 Palu. This problem appears since the teaching method is still teacher-centre-learning. This problem might be solved by using the Student Achievement Division (STAD) cooperative learning model. This study is a classroom action research that aims to increase interest and learning outcomes of accounting in students of class XI SMKN 2 Palu. Research carried out in two cycles which each cycle consists of four stages: planning, action implementation, observation and reflection. The results indicate that STAD type cooperative learning model used by the teacher is done very well and student interest in learning generally is very good especially on cycle II. It can be concluded that the use of STAD type cooperative learning model can increase interest and learning outcomes accounting students in class XI Ak 1 SMKN 2 Palu.